Coprocessing method for copper smelting slag and zinc leaching slag

Through the coordinated treatment of copper smelting slag and zinc leaching slag, the reduction and volatile treatment was carried out in the depletion furnace, which successfully improved the recovery rate of lead, zinc and copper, and solved the problem of resource waste in traditional treatment methods.

CN119464730APending Publication Date: 2025-02-18CINF ENG CO LTD

Patent Information

Application Number
CN202411644994.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the traditional treatment methods of copper smelting slag and wet zinc slurry, the recovery rates of zinc and lead are low, resulting in waste of resources and increased economic costs.

Method used

The coordinated treatment method of copper smelting slag and zinc leaching slag is adopted. By mixing and reducing volatile treatment in a depletion furnace, the reduction reaction is carried out by using a mixture of pulverized coal and air to generate zinc oxide soot and copper ice, thereby recovering lead Zinc and copper.

Benefits of technology

The recovery rate of lead and zinc is achieved by more than 80%, and the recovery rate of copper is greater than 85%, which significantly improves the comprehensive recycling and utilization rate of resources and reduces energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005139482930000011
    Figure HDA0005139482930000011
Patent Text Reader

Abstract

The invention belongs to the technical field of slag metallurgy, and relates to a coprocessing method for copper smelting slag and zinc leaching slag, which comprises the following steps: S1, mixing the copper smelting slag, the zinc leaching slag, a vulcanizing agent and a flux to obtain a mixture; introducing a mixture of pulverized coal and air, and reacting at 1150-1300 DEG C for 2-4 hours to obtain a gas phase, a slag phase and matte; s2, the gas phase is subjected to dust removal, and zinc oxide smoke dust rich in zinc, lead and silver is obtained; zinc is leached from the zinc oxide smoke dust through a wet method; and S3, the slag phase is subjected to slow cooling, ore grinding and copper flotation, copper concentrate is obtained, and gold, silver and copper elements are recycled. According to the method, heat of the high-zinc hot-state copper smelting slag is used for processing the high-copper normal-temperature zinc hydrometallurgy slag, and the slag processing energy consumption of the zinc hydrometallurgy slag is reduced. Through mixing treatment, lead and zinc in the mixed slag enter the secondary zinc oxide smoke dust to be recovered, and the recovery rate of the lead and the recovery rate of the zinc both reach 80% or above; and the total recovery rate of copper in the mixed slag is greater than 85% after copper enters matte recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slag metallurgy, and relates to a coordinated treatment method of copper smelting slag and zinc leaching slag. Background Art

[0002] Pyrometallurgy is the main method of copper smelting. Pyrometallurgy can be divided into two categories: molten pool smelting and flash smelting. Regardless of the type of pyrometallurgy, the copper smelting slag contains recoverable copper (0.5-5%) and other associated valuable metals such as zinc, lead, gold, and silver. At present, the main treatment method for copper smelting slag is the "hot slag slow cooling-crushing-grinding and flotation" process, which has a good recovery effect on copper, gold, and silver. The copper in the flotation tailings can be reduced to less than 0.3%, but it cannot effectively improve the recovery rate of zinc and lead. In the pyrometallurgy process, nearly 70% of the zinc in the copper concentrate raw material enters the smelting slag, and nearly 50% of the lead enters the smelting slag. The slag volume of the smelting slag is large, the zinc and lead grades are low, and most of them exist in the form of oxides, which are difficult to recover. As a result, in the copper smelting process, the recovery rate of zinc is generally less than 35%, and the recovery rate of lead is generally less than 50%. For copper concentrate raw materials with high zinc and lead content, such as some copper concentrates in Arab countries, which contain up to 4% to 8% zinc and up to 4% lead, how to improve the recovery rate of zinc and lead in the raw materials is an important factor affecting the economic feasibility of the project.

[0003] Hydrometallurgy is the main method of zinc smelting. Hydrometallurgy can be divided into two categories: roasting-leaching and direct leaching. All hydrometallurgy processes will produce a large amount of hydrometallurgy slag. On the one hand, hydrometallurgy slag is a hazardous waste and needs to be treated harmlessly by pyrometallurgy; on the other hand, hydrometallurgy slag contains valuable metals such as zinc, lead, copper, and silver, which have recycling value and can be recovered during the pyrometallurgy process. At present, the pyrometallurgy treatment processes of hydrometallurgy slag include rotary kiln volatilization, fuming, side-blowing smelting, etc., all of which require high energy consumption. During the pyrometallurgy fuming process, metals such as zinc, lead, and silver in the hydrometallurgy slag are volatilized and enriched in the secondary zinc oxide smoke, and the recovery rate can reach more than 80%; while more than 90% of the non-volatile copper is lost in the slag, and the recovery rate of copper is less than 10%. The copper content of zinc concentrate in Saudi Arabia is 0.8% to 1.96%. The copper leaching rate of conventional hydrometallurgical zinc smelting is about 35%, and the copper leaching rate of high temperature and high acid leaching is about 80%. The copper in zinc slag cannot be recovered. Therefore, it is necessary to strengthen the comprehensive recovery of the associated valuable metals in the concentrate and improve the comprehensive utilization rate of resources.

[0004] Prior art CN 106367605 B It relates to a production method of side-blown depleted copper smelting slag, comprising the following steps: adding a sulfiding agent and copper smelting slag into a side-blown depletion furnace from a feed port, wherein the mass ratio of the copper smelting slag to the sulfiding agent is 100:0-15, and the copper smelting slag is molten copper smelting slag or solid copper smelting slag; spraying fuel into a molten pool through a spray gun port arranged on the side of the depletion furnace, wherein the fuel is a mixture of pulverized coal and compressed air or a mixture of pulverized coal and oxygen-enriched air, stirring, heat transfer and mass transfer are carried out in the depletion furnace through the fuel, the temperature in the furnace is 1100-1300°C, the pressure is 0.1-0.4Mpa, and the depth of the molten pool is 800-2000mm; copper matte is discharged through a copper matte port, and depleted slag is discharged through a slag outlet; after cooling and dust collection, the flue gas enters a desulfurization system for desulfurization and emission up to standards; the process has the advantages of low investment, low energy consumption, low cost, high degree of automation, good environment, etc. However, this technology does not involve the recovery of zinc from copper smelting slag. During the treatment process, a large amount of Zn remains in the slag, which is not suitable for treating high-zinc copper smelting slag.

[0005] CN 107723470 A relates to a method for producing mixed slag containing copper and iron, which comprises the following steps: S1, slag mixing: adding copper slag to a smelting reaction device, adding one or more of lead smelting slag, blast furnace slag, steel slag and ferroalloy slag to form a mixed slag; adding one or more of copper oxide minerals, copper sulfide minerals and copper-containing materials at the same time; mixing evenly, heating the mixed slag to a molten state as a reaction slag, and monitoring the reaction slag in real time, and obtaining the slag after the reaction by regulation; S2, separation and recovery. The inventive method can not only process hot slag, making full use of molten copper slag and molten metallurgical slag, physical heat resources and hot metallurgical flux, but also process cold slag, and realize slag metallurgical modification through slag mixing or cold mixing; effectively solving the problem of efficient recycling of metallurgical resources and thermal energy and environmental pollution. However, this technology is aimed at high-iron and high-copper materials, and obtains iron-rich phase and copper-rich phase. Iron enters the iron-rich phase, resulting in less iron in the slag, which is mainly composed of CaO and SiO2 system. Therefore, CaO-SiO2 binary slag type is used to control the basicity CaO / SiO2 ratio of the reaction slag. However, the smelting temperature of this slag type is above 1320℃, which is higher than FeO-SiO2 and has higher energy consumption.

[0006] In summary, in the traditional copper smelting slag "hot slag slow cooling-crushing-grinding and flotation", zinc and lead are basically lost in the slag and cannot be recycled; and in the traditional hydrometallurgical treatment of zinc smelting slag alone, copper is basically lost in the slag and cannot be recovered. For copper smelting slag produced from high-zinc copper concentrate and hydrometallurgical zinc slag produced from high-copper zinc concentrate, it is urgent to solve the problem of low recovery rate of zinc in copper smelting slag and copper in hydrometallurgical zinc slag. Summary of the invention

[0007] The object of the present invention is to provide a method for the coordinated treatment of copper smelting slag and zinc leaching slag, so as to effectively extract lead and zinc elements in the copper smelting slag and copper elements in the hydrometallurgical zinc slag at the same time.

[0008] In order to achieve the above object, the main technical solutions adopted by the present invention are as follows:

[0009] A method for co-processing copper smelting slag and zinc leaching slag comprises the following steps:

[0010] S1, mixing copper smelting slag, zinc leaching slag, a sulfiding agent and a flux to obtain a mixture; then introducing a mixture of pulverized coal and air, reacting at 1150-1300° C. for 2-4 hours to obtain a gas phase, a slag phase and matte;

[0011] S2, dust removal in gas phase to obtain zinc oxide dust rich in zinc, lead and silver; zinc oxide dust is sent to wet leaching method;

[0012] S3. The slag phase is subjected to slow cooling, grinding, and flotation to obtain copper concentrate, and gold, silver, and copper elements are recovered.

[0013] Slow cooling: The sulfide phase in the slag can precipitate cuprous sulfide crystals and metallic copper particles during the sufficient cooling process. The slow cooling rate has a great influence on the size of the copper mineral grains precipitated in the slag. For example, most of the copper-containing grains are <5μm during water quenching. Such particles are difficult to separate from the slag body. Therefore, the cooling rate needs to be controlled to facilitate the growth of copper particles.

[0014] Grinding: After slow cooling and solidification, the slag is crushed and finely ground to separate the sulfide and metal particles from other components. Generally, it is necessary to finely grind to a particle size of -0.048mm to reach 90% to fully dissociate.

[0015] Flotation copper selection: The copper in the slag is basically a sulfide ore. Xanthate, pine oil, etc. are used to float the copper-containing substances into the flotation copper concentrate.

[0016] The processes and parameters for slow cooling, grinding and flotation of copper refer to the prior art CN202111358752.1.

[0017] In the smelting process of copper matte (melt of Cu2S and FeS), the stable copper compounds are Cu2S and Cu2O, and the iron compounds are FeO and FeS. These stable compounds will further react with each other or with other components in the raw materials. The reaction formula is: SiO2+Cu2O+FeS→Cu2S+FeO·SiO2.

[0018] Since the interfacial tension between FeS-Cu2S copper sulfur and 2FeO·SiO2 melt is about 0.02-0.06N / m, which is very small, copper sulfur is easily suspended in the slag; and the specific gravity of copper matte and slag phase is very different, so matte and slag can be stratified in the furnace.

[0019] Dust removal includes: flue gas → waste heat utilization of waste heat boiler → flue gas at waste heat boiler outlet → surface cooler → bag filter → fan → exhaust gas treatment (refer to the prior art Zhang Fubing. Process research on zinc smelting flue gas purification and waste acid treatment and comprehensive utilization [J]. Sulfuric Acid Industry, 2016, (05): 27-29).

[0020] Wet leaching of zinc includes: normal pressure leaching process, pressurized leaching process or normal pressure-pressurized combined leaching process (refer to prior art 202210614330.4 A method for oxygen pressure leaching of indium-containing zinc oxide dust).

[0021] In one preferred embodiment, the components of the zinc leaching slag include: Zn 3% to 20%, Cu 0.3% to 3%, Pb 1% to 5%, Fe 25% to 35%, and SiO2 3% to 10%.

[0022] In one preferred embodiment, the copper smelting slag comprises: Cu 0.76%-4.58%, Fe4 0.92%-45.99%, SiO2 25%-35%, Zn 4%-8%, and Pb 0.5%-3%.

[0023] In one preferred embodiment, the mass ratio of the copper smelting slag to the zinc leaching slag is 4:1-4:3.

[0024] In one preferred embodiment, in the copper smelting slag, Cu mainly exists in the form of Cu2S, followed by copper oxide and metallic copper.

[0025] In one preferred embodiment, in the copper smelting slag, Fe mainly exists in the form of iron silicate and magnetite, followed by hematite and iron sulfide.

[0026] In one preferred embodiment, the moisture content of the zinc leaching slag is below 8%.

[0027] Zinc leaching slag has high water content, the temperature of combustion tools (such as depletion furnace) is unstable, and the energy consumption is high.

[0028] In a preferred embodiment, the vulcanizing agent is one or more of sulfur, sulfate, sulfur oxide or sulfur-containing minerals.

[0029] In a preferred embodiment, the sulfur-containing mineral is one or more of pyrite, copper sulfide concentrate or oxygen-sulfur mixed zinc ore.

[0030] In one preferred embodiment, the mass ratio of Cu:S in the mixture is 3:1 to 4:1.

[0031] If the Cu:S mass ratio in the mixture is >4:1 and there is insufficient sulfur, elemental copper will be generated and enter the matte, thereby obtaining metallized matte, and even a matte-containing copper phase may appear; if the Cu:S mass ratio in the mixture is <3:1 and there is excess sulfur, FeS will be generated and enter the matte, the grade of the matte will be low, and the amount of slag will also increase.

[0032] In one preferred embodiment, the mass ratio of copper smelting slag to sulfidizing agent is 100:4-12.

[0033] The mass ratio of copper smelting slag and sulfiding agent is controlled to meet the mixed material Cu:S mass ratio of 3:1 to 4:1.

[0034] In one preferred embodiment, the flux is a material with a high SiO2 content, such as quartz, tridymite, and cristobalite.

[0035] In one of the preferred embodiments, the mass ratio of iron to silicon dioxide in the mixture is controlled to be Fe / SiO2=1.6-2.0.

[0036] If Fe / SiO2<1.6 or>2.0, the temperature in the furnace is required to be higher. If the temperature is not reached, the slag viscosity increases and the fluidity of the melt is poor.

[0037] Iron comes from copper smelting slag and zinc smelting slag, and no external addition is needed; copper smelting slag and zinc smelting slag contain SiO2, so external addition of SiO2 is usually required.

[0038] In one of the preferred embodiments, in the mixture of pulverized coal and air, the molar ratio of pulverized coal to oxygen is 1:0.5-0.7.

[0039] Pulverized coal is mainly C, and the reaction that occurs is: C+O2=CO2. If all C undergoes this reaction, the excess coefficient of oxygen is 1. If O2 is insufficient, C+CO2=2CO will occur, and a reducing atmosphere can be formed to reduce Zn, Pb, etc.

[0040] Pulverized coal is used as fuel and reducing agent, and the following reactions occur:

[0041] 2C+O2→2CO;

[0042] ZnO·Fe2O 3(液) +CO→ZnO (液) +2FeO (液) +CO2;

[0043] ZnO (液)+CO→Zn (气) +CO2;

[0044] PbO (液) +CO→Pb (气、液) +CO2;

[0045] In copper smelting slag, part of lead and zinc exist in the form of oxides and are thus reduced.

[0046] In one of the preferred embodiments, the excess air coefficient is 0.5-0.7.

[0047] When the excess air coefficient is 0.5-0.7, the reactions that occur are as follows:

[0048] Excess coefficient 0.5: C+0.5O2→CO

[0049] Excess coefficient 0.6: C+0.6O2→0.8CO+0.2CO2

[0050] Excess coefficient 0.7: C+0.7O2→0.6CO+0.4CO2

[0051] When the air excess coefficient is <0.5, carbon combustion is incomplete; as the excess coefficient increases, the amount of CO produced by carbon combustion decreases, and the reducing atmosphere becomes weaker, which is not conducive to the reduction and volatilization of valuable elements such as lead and zinc.

[0052] Control the reducing atmosphere. If there is excess oxygen, the sulfur will be oxidized and burned to produce SO2. After desulfurization, matte cannot be produced. If there is too little oxygen, the iron will be reduced to elemental iron, which has high viscosity and poor fluidity. In severe cases, the furnace may die.

[0053] The reaction temperature in S1 will significantly affect the fluidity. Too high a temperature will increase the consumption of pulverized coal, while too low a temperature will lead to poor melt fluidity.

[0054] The influence of the reaction time in S1 is: insufficient time leads to incomplete reaction, while too long time leads to high energy consumption.

[0055] In one preferred embodiment, the cooling rate of the slow cooling is no more than 10°C / min.

[0056] The sulfide phase in the slag can precipitate cuprous sulfide crystals and metallic copper particles during the process of sufficient slow cooling, and then can be mechanically separated by crushing and fine grinding. With the help of the difference in surface physical and chemical properties between them and other slag-forming components in the slag, sulfide slag concentrate can be floated and returned to the smelting process. The flotation slag tailings produced contain less than 0.3% copper and are treated as waste slag.

[0057] The slow cooling rate of the slag has a great influence on the size of the copper mineral grains precipitated in the slag. The cooling rate is preferably less than 10℃ / min. The cooled slag is ground to separate the sulfide and metal particles from other components. Generally, it needs to be finely ground to a particle size of -0.048mm to reach 90%.

[0058] The present invention is further explained below:

[0059] Add hot copper smelting slag into the depletion furnace, add cold material of wet zinc smelting slag, and appropriate amount of sulfiding agent and flux, spray a mixture of pulverized coal and air into the molten pool of the depletion furnace, control the reducing atmosphere and slag temperature in the depletion furnace, and let the slag stay in the furnace for a certain period of time. After the waste heat is recovered by the waste heat boiler, the depletion furnace gas enters the dust removal device, and the zinc, lead and silver volatilized in the depletion furnace gas are enriched in the zinc oxide smoke product obtained by dust removal, and the matte produced in the depletion furnace is intermittently discharged through the matte discharge port. After slow cooling and grinding, the depletion slag is floated to obtain copper concentrate, and the flotation copper concentrate is returned to the smelting ingredients. The flotation tailings contain less than 0.3% copper and are sold as raw materials for paving and building materials.

[0060] The beneficial effects of the present invention are:

[0061] During copper smelting, the recovery rate of zinc and lead in copper concentrate raw materials is generally less than 50%; while during zinc smelting, the recovery rate of copper is only about 35%, and the copper recovery rate of the high-temperature high-acid method can reach 80%. Even if the remaining copper enters the slag treatment, it cannot be recovered. The present invention utilizes the heat of high-zinc hot copper smelting slag to treat high-copper room-temperature wet zinc smelting slag, thereby reducing the slag treatment energy consumption of wet zinc smelting slag. The mixed slag is reduced and volatilized by a depletion furnace, and the lead and zinc in the mixed slag enter the secondary zinc oxide smoke and are recovered, and the recovery rates of lead and zinc are both above 80%; more than 65% of the copper in the mixed slag enters matte, and the copper remaining in the slag is recovered by slow cooling-grinding-flotation process, and the total recovery rate is greater than 85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the processing technology of the present invention. DETAILED DESCRIPTION

[0063] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] Embodiment 1:

[0065] like Figure 1As shown, 10t / h hot copper smelting slag (containing Cu 3%, Zn 5%, Pb 1%, Fe 41%, SiO2 30%) and 5t / h wet zinc smelting slag (containing Cu 1%, Zn 18%, Pb 3%, Fe 26%, SiO2 9%) are sent to the depletion furnace for reduction and volatilization treatment, pyrite is added as a sulfiding agent, the mass ratio of hot copper smelting slag and sulfiding agent is 100:6, and the mass ratio of Cu:S in the mixture is controlled to be 3.2:1; quartz is added to control the mass ratio of iron to silicon dioxide Fe / SiO2=1.6. A mixture of pulverized coal and air is sprayed into the molten pool of the depletion furnace, the molar ratio of pulverized coal to oxygen is 1:0.55, the depletion furnace is controlled to be a reducing atmosphere, the temperature is maintained at 1250℃, and the slag stays in the furnace for 2h.

[0066] After the reaction, the depleted furnace dust product is 2.6t of secondary zinc oxide (containing 0.25% Cu, 48.5% Zn, and 8.5% Pb), 0.4t of depleted furnace bottom copper matte (containing 62.12% Cu, 1.75% Zn, and 0.65% Pb), and 13.2t of depleted slag (containing 0.72% Cu, 1.0% Zn, and 0.2% Pb). The distribution rates of Cu in the secondary zinc oxide dust, copper matte, and slag are 1.86%, 70.99%, and 27.15% respectively; the distribution rates of Zn in the secondary zinc oxide dust, copper matte, and slag are 90.07%, 0.50%, and 9.43% respectively; the distribution rates of Pb in the secondary zinc oxide dust, copper matte, and slag are 88.40%, 1.04%, and 10.56% respectively.

[0067] The depleted slag was subjected to slow cooling, grinding, and flotation to select copper (the processes and parameters for slow cooling, grinding, and flotation to select copper refer to the prior art CN202111358752.1) to obtain 0.28t of copper concentrate (Cu 21.02%) and 12.92t of flotation tailings (Cu 0.28%), and the copper recovery rate of flotation was 61.94%.

[0068] During the treatment process, the total recovery rates of Cu, Zn and Pb were 88.96%, 89.51% and 88.40% respectively.

[0069] Example 2

[0070] 10t / h copper smelting slag (containing Cu 3%, Zn 5%, Pb 1%, Fe 40.92%, SiO2 25%) and 5t / h hydrometallurgical zinc slag (containing Cu 0.9%, Zn 5%, Pb 1%, Fe 25%, SiO2 10%) were sent to the depletion furnace for reduction and volatilization treatment, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag and sulfiding agent was 100:10, and the Cu:S in the mixture was controlled to be 3.5:1; quartz was added to control the mass ratio of iron to silicon dioxide Fe / SiO2 to 1.8:1. A mixture of pulverized coal and air was sprayed into the molten pool of the depletion furnace, the molar ratio of pulverized coal to oxygen was 1:0.65, the depletion furnace was controlled to be a reducing atmosphere, the temperature was maintained at 1280°C, and the slag stayed in the furnace for 2.5h.

[0071] After the reaction, the secondary zinc oxide product of the depleted furnace dust is 1.34t (containing 0.22% Cu, 46.1% Zn, 9.1% Pb), the depleted furnace bottom copper matte is 0.38t (containing 61.41% Cu, 2.11% Zn, 1.25% Pb), and the depleted slag is 15.53t (containing 0.70% Cu, 0.80% Zn, 0.15% Pb). The distribution rates of Cu in the secondary zinc oxide dust, copper matte, and slag are 0.85%, 67.64%, and 31.51% respectively; the distribution rates of Zn in the secondary zinc oxide dust, copper matte, and slag are 82.37%, 1.07%, and 16.57% respectively; the distribution rates of Pb in the secondary zinc oxide dust, copper matte, and slag are 81.29%, 3.18%, and 15.53% respectively.

[0072] The depleted slag was subjected to slow cooling, grinding, and flotation to select copper (the processes and parameters for slow cooling, grinding, and flotation to select copper refer to the prior art CN202111358752.1) to obtain 0.29t of copper concentrate (Cu 21.20%) and 15.24t of flotation tailings (Cu 0.31%), with a flotation copper recovery rate of 56.54%.

[0073] During the treatment process, the total recovery rates of Cu, Zn and Pb were 85.93%, 82.37% and 81.29% respectively.

[0074] Example 3

[0075] 10t / h copper smelting slag (containing Cu 0.76%, Zn 8%, Pb 3%, Fe 42%, SiO2 35%) and 2.5t / h hydrometallurgical zinc slag (containing Cu 3%, Zn 20%, Pb 1%, Fe 35%, SiO2 3%) were sent to the depletion furnace for reduction and volatilization treatment, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag and sulfiding agent was 100:12, and the mass ratio of Cu:S in the mixture was controlled to be 3.6:1; quartz was added to control the mass ratio of iron to silicon dioxide Fe / SiO2=1.6. A mixture of pulverized coal and air was sprayed into the molten pool of the depletion furnace, the molar ratio of pulverized coal to oxygen was 1:0.50, the depletion furnace was controlled to be a reducing atmosphere, the temperature was maintained at 1300℃, and the slag stayed in the furnace for 2h.

[0076] After the reaction, the depleted furnace dust product is 2.4t of secondary zinc oxide (containing 0.08% Cu, 44.90% Zn, and 12.10% Pb), 0.18t of depleted furnace bottom copper matte (containing 57.34% Cu, 2.22% Zn, and 1.63% Pb), and 10.92t of depleted slag (containing 0.42% Cu, 2.0% Zn, and 0.29% Pb). The distribution rates of Cu in the secondary zinc oxide dust, copper matte, and slag are 1.27%, 68.35%, and 30.37% respectively; the distribution rates of Zn in the secondary zinc oxide dust, copper matte, and slag are 82.89%, 0.31%, and 16.80% respectively; the distribution rates of Pb in the secondary zinc oxide dust, copper matte, and slag are 89.35%, 0.90%, and 9.74% respectively.

[0077] The depleted slag is subjected to slow cooling, grinding, and flotation to select copper (the processes and parameters for slow cooling, grinding, and flotation to select copper refer to the prior art CN202111358752.1) to obtain 0.1t of copper concentrate (Cu 24.22%) and 10.82t of flotation tailings (Cu 0.20%), and the copper recovery rate of flotation is 52.82%.

[0078] During the treatment process, the total recovery rates of Cu, Zn and Pb were 85.70%, 82.89% and 89.35% respectively.

[0079] Example 4

[0080] 10t / h copper smelting slag (containing Cu 4.58%, Zn 4%, Pb 0.5%, Fe 41%, SiO2 30%) and 5t / h hydrometallurgical zinc slag (containing Cu 0.5%, Zn 15%, Pb 5%, Fe 30%, SiO2 5%) were sent to the depletion furnace for reduction and volatilization treatment, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag and sulfiding agent was 100:4, and the mass ratio of Cu:S in the mixture was controlled to be 3.5:1; quartz was added to control the mass ratio of iron to silicon dioxide Fe / SiO2=2. A mixture of pulverized coal and air was sprayed into the molten pool of the depletion furnace, the molar ratio of pulverized coal to oxygen was 1:0.7, the depletion furnace was controlled to be a reducing atmosphere, the temperature was maintained at 1200℃, and the slag stayed in the furnace for 4h.

[0081] After the reaction, the secondary zinc oxide product 2.2t (containing 0.30% Cu, 45.90% Zn, 11.70% Pb), the depleted furnace bottom copper matte 0.52t (containing 68.28% Cu, 0.52% Zn, 0.67% Pb), and the depleted slag 13.48t (containing 0.90% Cu, 1.02% Zn, 0.29%) were obtained. The distribution rates of Cu in the secondary zinc oxide dust, copper matte, and slag were 1.37%, 73.52%, and 25.12% respectively; the distribution rates of Zn in the secondary zinc oxide dust, copper matte, and slag were 87.81%, 0.24%, and 11.96% respectively; the distribution rates of Pb in the secondary zinc oxide dust, copper matte, and slag were 85.80%, 1.17%, and 13.03% respectively.

[0082] The depleted slag was subjected to slow cooling, grinding, and flotation to select copper (the processes and parameters for slow cooling, grinding, and flotation to select copper refer to the prior art CN202111358752.1) to obtain 0.34t of copper concentrate (Cu 24.09%) and 13.14t of flotation tailings (Cu 0.30%), and the copper recovery rate of flotation was 67.51%.

[0083] During the treatment process, the total recovery rates of Cu, Zn and Pb were 91.39%, 87.81% and 85.80% respectively.

[0084] Example 5

[0085] 8t / h copper smelting slag (containing Cu 4.58%, Zn 4%, Pb 0.5%, Fe 41%, SiO2 30%) and 6t / h hydrometallurgical zinc slag (containing Cu 0.5%, Zn 15%, Pb 5%, Fe 30%, SiO2 5%) were sent to the depletion furnace for reduction and volatilization treatment, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag and sulfiding agent was 100:4, and the mass ratio of Cu:S in the mixture was controlled to be 3.7:1; quartz was added to control the mass ratio of iron to silicon dioxide Fe / SiO2=2. A mixture of pulverized coal and air was sprayed into the molten pool of the depletion furnace, the molar ratio of pulverized coal to oxygen was 1:0.7, the depletion furnace was controlled to be a reducing atmosphere, the temperature was maintained at 1200℃, and the slag stayed in the furnace for 4h.

[0086] After the reaction, the secondary zinc oxide product 2.25t (containing 0.28% Cu, 48.12% Zn, 13.85% Pb), the depleted furnace bottom copper matte 0.48t (containing 60.10% Cu, 0.73% Zn, 0.75% Pb), and the depleted slag 12.39t (containing 0.82% Cu, 1.08% Zn, 0.20% Pb) were obtained. The distribution rates of Cu in the secondary zinc oxide dust, copper matte, and slag were 1.59%, 72.78%, and 25.63% respectively; the distribution rates of Zn in the secondary zinc oxide dust, copper matte, and slag were 88.75%, 0.29%, and 10.97% respectively; the distribution rates of Pb in the secondary zinc oxide dust, copper matte, and slag were 91.65%, 1.06%, and 7.29% respectively.

[0087] The depleted slag was subjected to slow cooling, grinding, and flotation to select copper (the processes and parameters for slow cooling, grinding, and flotation to select copper refer to the prior art CN202111358752.1) to obtain 0.34t of copper concentrate (Cu 19.25%) and 12.05t of flotation tailings (Cu 0.30%), and the copper recovery rate of flotation was 64.42%.

[0088] In the treatment process, the total recovery rates of Cu, Zn and Pb were 90.31%, 88.75% and 91.65% respectively.

[0089] Comparative Example 1

[0090] On the basis of Example 1, instead of using the copper smelting slag and the hydrometallurgical zinc smelting slag for coordinated treatment, the copper smelting slag and the hydrometallurgical zinc smelting slag are directly fed into the depletion furnace separately for reduction volatilization treatment. Other raw materials and steps are the same as those in Example 1.

[0091] The results show that when copper smelting slag is treated alone, the total recovery rates of Zn and Pb are 75.68% and 72.30% in the treatment process, and the recovery rates of lead and zinc are both less than 80%; when wet zinc smelting slag is treated alone, because the material contains less copper, after the reaction, no matte layer can be obtained at the bottom of the depleted furnace, and copper is dispersed in the slag, which needs to be recovered in the slow cooling, grinding, and flotation copper selection process. The copper recovery rate of the whole process is only 64.38%. In addition, the separate treatment of room temperature wet zinc smelting slag requires complete reliance on external energy for heating and melting, which consumes a lot of energy; the two materials are treated separately, and the number of equipment is large, and the production cost is high.

[0092] Comparative Example 2

[0093] On the basis of Example 1, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag to the sulfiding agent was 100:2, and the Cu:S in the mixture was controlled to be 4.2:1. Other raw materials and steps were the same as in Example 1.

[0094] The results showed that part of the copper in the mixture was not combined with sulfur, but existed in the form of elemental copper. Most of it entered the matte to obtain metallized matte, and a small amount was mixed in the depleted slag. The elemental copper could not be recovered during the flotation process. The copper recovery rate of the flotation process was 41.54%, the tailings contained 0.43% copper, and the copper recovery rate of the whole process was 83.04%.

[0095] Comparative Example 3

[0096] On the basis of Example 1, pyrite was added as a sulfiding agent, the mass ratio of hot copper smelting slag to the sulfiding agent was 100:14, Cu:S in the mixture was controlled to be 2.8:1, and other raw materials and steps were the same as Example 1. It was found that: the consumption of the sulfiding agent was large, the amount of smelting slag was large; and part of the iron in the mixture combined with sulfur to generate FeS that entered the matte, the copper grade in the matte was reduced to 58.40%, and the amount of slag in the subsequent blowing process was large.

[0097] Comparative Example 4

[0098] On the basis of Example 1, quartz stone was added to control the mass ratio of iron to silicon dioxide Fe / SiO2=1.4, and other raw materials and steps were the same as Example 1.

[0099] The results show that the smelting temperature of the mixed slag needs to be controlled at 1410℃ so that the slag can obtain good fluidity.

[0100] Comparative Example 5

[0101] On the basis of Example 1, quartz stone was added to control the mass ratio of iron to silicon dioxide Fe / SiO2 to 2.1, and other raw materials and steps were the same as Example 1.

[0102] The results show that the smelting temperature of the mixed slag needs to be controlled at 1420℃ so that the slag can obtain good fluidity.

[0103] Comparative Example 6

[0104] On the basis of Example 1, a mixture of pulverized coal and air is sprayed into the molten pool of the depletion furnace to control the depletion furnace to have a reducing atmosphere with an excess air coefficient of 0.45. Other raw materials and steps are the same as in Example 1.

[0105] The results showed that the pulverized coal was not fully burned and the reducing atmosphere was weak, and the secondary zinc oxide dust contained 2.5t of zinc (Zn 44.2%, Pb 7.76%) and 13.3t of depleted slag (Zn 1.8%, Pb 0.35%). The distribution rates of Zn and Pb in the secondary zinc oxide dust were 78.93% and 77.60% respectively, and the volatility of Zn and Pb was low.

[0106] Comparative Example 7

[0107] On the basis of Example 1, a mixture of pulverized coal and air is sprayed into the molten pool of the depletion furnace to control the depletion furnace to have a reducing atmosphere with an excess air coefficient of 0.75. Other raw materials and steps are the same as in Example 1.

[0108] The results showed that the amount of CO produced by pulverized coal combustion decreased, the reducing atmosphere became weaker, and the secondary zinc oxide dust contained 2.45t of zinc (Zn 43.8%, Pb 7.5%) and 13.35t of depleted slag (Zn 1.9%, Pb 0.4%). The distribution rates of Zn and Pb in the secondary zinc oxide dust were 76.65% and 73.5% respectively, and the volatilization rates of Zn and Pb decreased.

[0109] Comparative Example 8

[0110] On the basis of Example 1, the reaction temperature after the mixture of pulverized coal and air is introduced is set to 1100° C., and the other raw materials and steps are the same as in Example 1.

[0111] The results showed that the furnace condition was not good and the melt fluidity was poor, which affected the slag and matte discharge operations.

[0112] Comparative Example 9

[0113] Based on Example 1, the difference is that the temperature is maintained at 1520°C, and the other raw materials and steps are the same as Example 1.

[0114] The results showed that the melt fluidity was good, but the coal rate increased by 8% and the energy consumption was high.

[0115] Comparative Example 10

[0116] On the basis of Example 1, the composition of the zinc leaching slag was changed, and the zinc leaching slag contained Zn 18%, Pb 3%, Cu 0.2%, Fe 26%, and SiO2 9%. Other raw materials and steps were the same as in Example 1.

[0117] The results showed that due to the reduction of copper content in the mixture, the matte layer formed in the depletion furnace was thin, the stratification effect of matte and depletion slag was poor, and the distribution rate of copper in matte was 62.88%. The depletion slag was subjected to slow cooling, grinding, and flotation to select copper, and 0.28t of copper concentrate (Cu 21.65%) and 12.96t of flotation tailings (Cu 0.37%) were obtained, and the copper recovery rate of flotation was 55.83%. In the treatment process, the total recovery rate of Cu was 83.61%.

[0118] Comparative Example 11

[0119] On the basis of Example 1, the composition of the copper smelting slag was changed. The copper smelting slag contained Cu 3%, Zn 2%, Pb 1%, Fe 41%, and SiO2 30%. Other raw materials and steps were the same as in Example 1.

[0120] The results showed that after the reaction, 1.93t of depleted furnace dust product (containing 47.50% Zn and 10.75% Pb) and 13.87t of depleted furnace slag (containing 1.3% Zn and 0.22% Pb) were obtained. In the treatment process, the total recovery rates of Zn and Pb were 83.34% and 82.99% respectively.

[0121] Comparative Example 12:

[0122] 25 t / h copper smelting slag (containing Cu 3%, Zn 5%, Pb 1%, Fe 41%, SiO2 30%) and 5 t / h hydrometallurgical zinc slag (containing Cu 1%, Zn 18%, Pb 3%, Fe 26%, SiO2 9%) were sent to the depletion furnace for reduction volatilization treatment. Other raw materials and steps were the same as in Example 1.

[0123] The results showed that after the reaction, 3.38t of depleted furnace dust product (containing 48.3% Zn and 9.4% Pb) and 28.12t of depleted furnace slag (containing 1.80% Zn and 0.20% Pb) were obtained. In the treatment process, the total recovery rates of Zn and Pb were 75.93% and 79.43% respectively.

[0124] Comparative Example 13:

[0125] 10 t / h of copper smelting slag (containing Cu 3%, Zn 5%, Pb 1%, Fe 41%, SiO2 30%) and 10 t / h of hydrometallurgical zinc smelting slag (containing Cu 1%, Zn 18%, Pb 3%, Fe 26%, SiO2 9%) were fed into a depletion furnace for reduction volatilization treatment. Other raw materials and steps were the same as in Example 1.

[0126] The results showed that after the reaction, 0.42t of matte copper (including 62.0% Cu) and 17.33t of depleted slag (including 0.75% Cu) were obtained. The depleted slag was subjected to slow cooling, grinding, and flotation to separate copper, and 0.33t of copper concentrate (21.87% Cu) and 17.00t of flotation tailings (0.34% Cu) were obtained. The copper recovery rate of flotation was 55.53%. In the treatment process, the total recovery rate of Cu was 84.48%.

[0127] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for co-processing copper smelting slag and zinc leaching slag, characterized in that: The following steps are involved: S1, mixing copper smelting slag, zinc leaching slag, a sulfiding agent and a flux to obtain a mixture; then introducing a mixture of pulverized coal and air, reacting at 1150-1300° C. for 2-4 hours to obtain a gas phase, a slag phase and matte; S2, dust removal in gas phase to obtain zinc oxide dust rich in zinc, lead and silver; Zinc is leached out by wet method using zinc oxide dust; S3. The slag phase is subjected to slow cooling, grinding, and flotation to select copper to obtain copper concentrate and recover gold, silver, and copper elements.

2. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: The components of the zinc leaching slag include: Zn 3%-20%, Cu 0.3%-3%, Pb 1%-5%, Fe 25%-35%, SiO2 3%-10%; the components of the copper smelting slag include: Cu 0.76%-4.58%, Fe 40.92%-45.99%, SiO2 25%-35%, Zn 4%-8%, Pb 0.5%-3%.

3. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: The mass ratio of the copper smelting slag to the zinc leaching slag is 4:1-4:

3.

4. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: The vulcanizing agent is one or more of sulfur, sulfate, sulfur oxide or sulfur-containing minerals.

5. The method for co-processing copper smelting slag and zinc leaching slag according to claim 4, characterized in that: The sulfur-containing mineral is one or more of pyrite, copper sulfide concentrate or oxygen-sulfur mixed zinc ore.

6. The method for co-processing copper smelting slag and zinc leaching slag according to any one of claims 1 to 5, characterized in that: The mass ratio of Cu:S in the mixture is 3:1 to 4:

1.

7. The method for co-processing copper smelting slag and zinc leaching slag according to any one of claims 1 to 5, characterized in that: The mass ratio of copper smelting slag to sulfidizing agent is 100:4-12.

8. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: The mass ratio of iron to silicon dioxide in the mixture is controlled to be Fe / SiO2=1.6-2.

0.

9. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: Excess air coefficient 0.5~0.

7.

10. The method for co-processing copper smelting slag and zinc leaching slag according to claim 1, characterized in that: The cooling rate of slow cooling is not more than 10°C / min.

Citation Information

Patent Citations

  • A kind of production method of side-blowing depleted copper smelting slag

    CN106367605B

  • Method for producing copper and iron containing mixed slag

    CN107723470A

  • Method for efficiently recovering copper and iron metals in copper smelting slag

    CN114260099A

  • Oxygen pressure leaching method for indium-containing zinc oxide smoke dust

    CN114836627A

Cited By

  • Self-heating tempering and valuable metal partition recycling method for copper smelting slag

    CN119951860A

  • Method for preparing crude copper by smelting copper oxide ore and pyrite

    CN121802181A

  • Method for smelting copper oxide ore and pyrite to produce crude copper

    CN121802181B